2008
DOI: 10.1007/s00270-008-9399-0
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative DynaCT Detection and Immediate Correction of a Type 1a Endoleak Following Endovascular Repair of Abdominal Aortic Aneurysm

Abstract: Reintervention following endovascular aneurysm repair (EVAR) is required in up to 10% of patients at 30 days and is associated with a demonstrable risk of increased mortality. Completion angiography cannot detect all graft-related anomalies and computed tomographic angiography is therefore mandatory to ensure clinical success. Intraoperative angiographic computed tomography (DynaCT; Siemens, Germany) utilizes cone beam reconstruction software and flat-panel detectors to generate CT-like images from rotational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…In fact, case reports have been published showing CBCT is able to detect an endoleak where angiography fails to do so. 4,5 We did not perform completion angiography in conjunction with completion CBCT to avoid the additional radiation and contrast loads. As such, direct comparison of sensitivity and specificity of endoleak identification between angiography and CBCT is not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, case reports have been published showing CBCT is able to detect an endoleak where angiography fails to do so. 4,5 We did not perform completion angiography in conjunction with completion CBCT to avoid the additional radiation and contrast loads. As such, direct comparison of sensitivity and specificity of endoleak identification between angiography and CBCT is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary experience has demonstrated its potential utility in pre-and postdeployment scenarios. [1][2][3][4][5] One of the most potentially useful applications of CBCT is intraoperatively to guide the performance of fluoroscopy-driven procedures using fusion of CT images and fluoroscopy, similar to traditional "roadmapping." Intraoperative CBCT images can be registered, or fused, with preoperative MDCT allowing the MDCT image to be superimposed on the live fluoroscopic image.…”
mentioning
confidence: 99%
“…Others have demonstrated that FluoroCT has been capable of identifying the source of an endoleak when the location was not clear on conventional MDCT. 15 Used in this fashion, however, FluoroCT may prove overly sensitive with a high false-positive rate. This may be particularly true in the identification of type II endoleaks.…”
Section: Rotational Angiography and Fluoroscopic Computed Tomography mentioning
confidence: 99%
“…Although conventional fluoroscopy is used for intraoperative PCNL imaging, noncontrast CT carries more detailed information regarding stone size and location, soft tissue structures, and location of body structures for percutaneous access in PCNL. Fluorosocopy provides several advantages: (1) It is widely available; (2) it is easy to use; (3) mobility of a C-arm apparatus adapts to a wide array of operative settings.…”
Section: Introductionmentioning
confidence: 99%